The effects of subject pool and design experience on rationality in experimental asset markets - Lucy F. Ackert; Bryan K. Church (Federal Reserve Bank of Atlanta, 1998)
Empirical evidence suggests that prices do not always reflect fundamental values and individual behavior is often inconsistent with rational expectations theory. We report the results of fourteen experimental markets designed to examine whether the interactive effect of subject pool and design experience tempers price bubbles and improves forecasting ability. Our main findings are: (i) price run-ups are modest and dissipate quickly when traders are knowledgeable about financial markets and have design experience; (ii) price bubbles moderate quickly when only a subset of traders are knowledgeable and experienced; and (iii) individual forecasts of price are not consistent with the predictions of the rational expectations model in any market.
Keywords: 330; Financial markets